(untitled) (Law, State and Telecommunications Review, 2010)
This article presents (1) the material technical characteristics of Mobile TV, its difference with IPTV and Internet TV, (2) the network, spectrum and equipment issues that will influence the legal framework, (3) the opportunities for Mobile TV resulting from the digital switchover, and (4) a case study of Mexico regarding the legal framework of broadcasting and telecommunication services, the market players, spectrum availability, the digital switchover and other outstanding issues for Mobile TV.